Utilisation of recycled concrete aggregates in asphalt mixture - Lau, Kia Kgoon. (2012)
The feasibility of full substitution of coarse and fine recycled concrete aggregates (RCA) into porous asphalt (PA) mixture for light traffic road pavement construction, in particular pedestrian and bicycle paths, were investigated in this project. Besides investigating the use of RCA in the PA mixture, the effects of three filler types (RCA filler, hydrated lime and kaolin) on the asphalt mixture were also examined. Nine small specimens and two large PA specimens incorporating each filler type were batched for performance testing. The mix design followed earlier research project by Yeung (2009).